Exploring the development of oral skills and social competences through role-plays in an English language subject in higher education - Martínez Lirola, María (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2024)
Contemporary English teaching demands the use of methodologies that facilitate students’ participation and protagonism in the teaching-learning process. This paper proposes the use of role-plays framed in a cooperative methodology in order to encourage students’ participation and the acquisition of social competences in an advanced EFL subject at higher education. The objectives of this article are: 1. To promote the development of oral skills and social competences through students’ participation in role- plays and 2. To know students opinions about the implementation of roles-plays in the classroom. The study uses a mixed-methods research design by observing the students’ performances in role-plays and by using a questionnaire at the end of the semester. Findings show that students acquire social competences, increase their interaction and improve their speaking skills by their participation in role- plays. Moreover, the study revealed that students become more aware of social situations.